Optimization and elucidation of interactions between ammonium, nitrate and phosphate in Centella asiatica cell culture using response surface methodology - Omar, Rozita; Abdullah, M. A.; Hasan, M. A.; Mahmood, Maziah; Mustapa Kamal, Siti Mazlina (Springer, 2005)

(untitled)
The effects of macronutrients (NO3−, NH4+ and PO43−) on cell growth and triterpenoids production inCentella asiatica cell suspension cultures were analyzed using the Box-Behnken response surface model experimental design. In screening and optimization experiments, PO43− as a single factor significantly influenced cell growth where increasing the phosphate level from 0.1 to 2.4 or 2.6 mM, elevated cell growth from 3.9 to 14-16 g/L. The optimum values predicted from the response surface model are 5.05 mM NH4+, 15.0 mM NO3− and 2.6 mM PO43−, yielding 16.0 g/L cell dry weight with 99% fitness to the experimental data. While the NH4+-NO3− interaction influenced cell growth positively in the optimization experiment, NH4+ and NO3− as single factors; and interactions of NO3−-PO43−, NH4+-PO43− and NH4+-NO3− were all negative in the screening experiment. Cell growth and the final pH level were positively affected by PO43−, but negatively affected by NH4+ and NH4+-PO43− interactions. The different effects of factors and their interactions on cell growth and final pH are influenced by a broad or narrow range of macronutrient concentrations. The productions of triterpenoids however were lower than 4 mg/g cell dry weight.